Compact type-I coil planet centrifuge for counter-current chromatography - Yang, Yi (2010)
A compact type-I coil planet centrifuge has been developed for performing counter-current chromatography. It has a revolution radius of 10 cm and a column holder height of 5 cm compared with 37 cm and 50 cm in the original prototype, respectively. The reduction in the revolution radius and column length permits application of higher revolution speed and more stable balancing of the rotor which leads us to learn more about its performance and the future potential of type-I coil planet centrifuge. The chromatographic performance of this apparatus was evaluated in terms of retention of the stationary phase (Sf), peak resolution (Rs), theoretical plate (N) and peak retention time (t(R)). The results of the experiment indicated that increasing the revolution speed slightly improved both the retention of the stationary phase and the peak resolution while the separation time is remarkably shortened to yield an excellent peak resolution at a revolution speed of 800 rpm. With a 12 ml capacity coiled column, DNP-glu, DNP-β-ala and DNP-ala were resolved at Rs of 2.75 and 2.16 within 90 min at a flow rate of 0.4 ml/min. We believe that the compact type-I coil planet centrifuge has a high analytical potential.